Spatial and Temporal Variability in Antineoplastic Drug Surface Contamination in Cancer Care Centers in Alberta and Minnesota. Issue 7 (23rd April 2021) - Jeronimo, Matthew; Arnold, Susan; Astrakianakis, George; Lyden, Grace; Stewart, Quinn; Petersen, Ashley; Chambers, Carole; Malard Johnson, Darcy; Zimdars, Emily; Kaup, Hannah; Davies, Hugh W
Abstract: The health risks of exposure to antineoplastic drugs (ADs) are well established, and healthcare professionals can be exposed while caring for cancer patients receiving AD therapy. Studies conducted worldwide over the past two decades indicate continuing widespread surface contamination by ADs. No occupational exposure limits have been established for ADs, but concerns over exposures have led to the development of guidelines, such as United States Pharmacopeia (USP) General Chapter <800> Hazardous Drugs—Handling in Healthcare. While recommending regular surveillance for surface contamination by ADs these guidelines do not provide guidance on sampling strategies. Better characterization of spatial and temporal variability of multidrug contamination would help to inform such strategies. We conducted surface-wipe monitoring of nine cancer care centers in Alberta, Canada and Minnesota, USA, with each center sampled eight times over a 12-month period. Twenty surfaces from within pharmacy and drug administration areas were sampled, and 11 drugs were analyzed from each wipe sample. Exposure data were highly left-censored which restricted data analysis; we examined prevalence of samples above limit of detection (LOD), and used the 90th percentile of the exposure distribution as a measure of level of contamination. We collected 1984 wipe samples over a total of 75 sampling days resulting in 21 824 observations. Forty-five percent of wipe samples detected at least one drug above the LOD, but only three of the drugs had more than 10% of observations above the LOD: gemcitabine (GEM) (24%), cyclophosphamide (CP) (16%), and paclitaxel (13%). Of 741 wipe samples with at least one drug above LOD, 60% had a single drug above LOD, 19% had two drugs, and 21% had three drugs or more; the maximum number of drugs found above LOD on one wipe was 8. Surfaces in the compounding area of the pharmacy and in the patient area showed the highest prevalence of samples above the LOD, including the compounding work surface, drug fridge handle, clean room cart, passthrough tray, and hazardous drug room temperature storage, the IV pump keypad, patient washroom toilet handle, patient washroom door handle, nurses' storage shelf/tray, and patient side table. Over the course of the study, both 90th percentiles and prevalence above LOD varied without clear temporal patterns, although some centers appeared to show decreasing levels with time. Within centers, the degree of variability was high, with some centers showing changes of two to three orders of magnitude in the 90th percentile of drug concentrations month to month. A clear difference was observed between the six centers located in Alberta and the three in Minnesota, with Minnesota centers having substantially higher percentages of samples above the LOD for CP and GEM. Other factors that were associated with significant variability in exposures were drug compounding volume, size of center, number of patients seen, and age of the center. We hope that demonstrating variability associated with drug, surface, clinic-factors, and time will aid in a better understanding of the nature of AD contamination, and inform improved sampling strategies.